Resource management in advanced wireless networks - Suresh, A.; Ramkumar, J.; Baskar, M.; Bashir, Ali Kashif (Wiley, 2023)
RESOURCE MANAGEMENT IN ADVANCED WIRELESS NETWORKS Written and edited by a team of experts in the field, this exciting new volume provides a comprehensive exploration of cutting-edge technologies and trends in managing resources in advanced wireless networks. This groundbreaking new volume from Wiley-Scrivener discusses the challenges that are emerging while managing the resources in various wireless networking technologies. Initially, the evolution of wireless networking technologies is presented, focusing on the advantages of improving data rates and data reliability. The book then goes through the various architecture designs based on the network paradigms, along with the evolution of networks based on the trends in the telecommunication industry. Various salient features are highlighted in managing resources, and the role of routing strategies is addressed with regard to real-time applications. Covering resource management in wireless networks, various industries are covered, such as healthcare and financial services, but the ideas are useful across many industries. Whether for the veteran engineer, industry professional, or student, this is a must- have for any library.
Includes bibliographical references and index. - Online resource; title from PDF title page (John Wiley, viewed October 23, 2023)
Keywords: Radio resource management (Wireless communications); Ressources radio; Gestion